Supplier Development: BP Azerbaijan - Sadikhova, Narmina (2007)
With more and more manufacturing companies outsourcing their activities in the modern business world, the suppliers' performance is becoming a major determinant of the purchasing company's success. In such circumstances supplier development became a hot topic in the operations literature. Any effort of the purchasing company to improve supplier's performance can be defined as supplier development. This dissertation examines motives and factors influencing the purchasing company to engage in various supplier development activities. It presents various strategies and activities that the companies can choose from, highlights implementations steps of those activities and presents barriers that might be faced along with actions to overcome them. Theoretical findings of various researchers are illustrated through a case-study organisation - BP Azerbaijan. It was chosen due to the fact that BP is a leading investor in the country with very limited local supplier base, which has motivated the company to have set a target to increase their local supply base. Thus, they are engaged in various development initiatives, which are described along challenges that may arise and suggestions as to how these challenges might be overcome.